PENDAYAGUNAAN KONTEKS PERCAKAPAN ANAK USIA 3 TAHUN DALAM KOMUNIKASI INTERPERSONAL ANAK DI LINGKUNGAN KELUARGA - Dhini, Maudy Sukma; Eko Rusminto, Nurlaksana; Munaris, Munaris; Widodo, Mulyanto; Samhati, Siti (Universitas Hamzanwadi, 2024)
The aim of this research is to examine the conversational context of 3 year old children in interpersonal communication in the family environment. The context of the conversation of the research subject is the conversation carried out by the subject with all members of his family, namely father, mother and grandmother. The type of research is descriptive qualitative research, the analysis was carried out on a 3 year old child named Haura who lives in Terbanggi Besar, Lampung. Based on the results, it can be seen how overall the dialogue can be answered well by the subject with very good responses in dialogue with family members. There are still pronunciation errors and the loss of some foems in conversations between subjects and family members. This pronunciation error is very normal because some consonants are difficult for 3 year old children to pronounce, this can be caused by environmental factors which may not teach sound pronunciation correctly and continuously. Therefore, in this dialogue, it can be said that the interpersonal conversation between the subject and the family members is in the good category because they can understand the question sentences asked by the family members well even though the pronunciation is unclear due to difficulty pronouncing phoneme sounds that are unfamiliar to hear and difficult to imitate.